Clinical and cardiovascular alterations produced by scorpion envenomation in dogs - Cordeiro, F. F. [UNESP]; Sakate, M. [UNESP]; Fernandes, V. [UNESP]; Cuyumjian, P. R. (FapUNIFESP (SciELO), 2006)
Scorpionism is a common problem that occurs in tropical and subtropical countries and assumes great medical-sanitary importance due to its fatal effect on sensitive individuals, being able to lead children and aged people to death. The envenomation lethal potential is responsible for the serious cardiopulmonary alterations the scorpion toxin produces in its victims. The present research evaluated the effects of Tityus serrulatus venom on dogs, using two distinct doses: a dose that simulates natural envenomation (0.4 mg/total dose), and an experimental dose (0.25 mg/kg). General clinical signs were observed at different moments after envenomation, and specific data related to the cardiopulmonary system were evaluated by systemic arterial pressure measurement, CK-MB enzymatic activity dosage, and radiographic, electrocardiographic and echocardiographic examinations. Results demonstrated that the scorpion venom, in experimental doses, was able to cause acute and reversible cardiac injury in few days, and, in the dose that simulated natural accident, it produced clinical signs of light envenomation, such as local pain, hyperesthesia, sialorrhea, vomiting, diarrhea, sneeze and prostration.
Keywords: Cardiopulmonary alterations; Dogs; Scorpion; Tityus serrulatus; Canis familiaris; Scorpiones